Groundfish surveys in the Atlantic Iberian waters (ICES Divisions VIIIc and IXa): history and perspectives - Cardador, Fátima; Sánchez-Delgado, Francisco; Pereiro-Muñoz, Francisco Javier; Borges, María de Fátima; Caramelo, Ana María; Azevedo, Manuela; Silva, Alexandra; Pérez-Contreras, María Nélida; Martins, María; Olaso-Toca, Luis Ignacio; Pestana, Graça; Trujillo-Gorbea, Valentín; et al. (1997)
Spanish Oceanogrnphic Institute (IEO) and Portuguese Research Inistitute (IPIMAR, ex-INIP) using their research vessels "Comide de Saavedra" and "Noruega" have conducted groundfish surveys in Spanish and Portuguese waters. The results of these surveys have been reported to the relevant ICES Working Groups, communicated to ICES Annual Conferences and/or published in journals of bioiogy and flsheries. Data collected from groundfish surveys were also the basis to carry out assemblage studies and to several advices to the Spanish, Porttuguese and European fishery administrations concerning the implementation of technical measures for fish stock management. This communication intends to give information about the past, the present and the future of these surveys, concerning objectives, methodology and publications. Critical aspects and solutions to improve some aspects are presented.